Taking sides clashing views on controversial African issues (McGraw-Hill/Dushkin, 2004)
This debate-style reader is designed to introduce students to controversies in African Studies. The readings, which represent the arguments of leading historians, political scientists, and economists, reflect a variety of viewpoints, and have been selected for their substance, liveliness and relevance. By requiring students to analyze opposing viewpoints and reach considered judgments, Taking Sides actively develops critical thinking skills.